Mathematical modeling of cleaning dust-laden gas flows in the cyclone dust collector - Серебрянський, Дмитро Олександрович; Плашихін, Сергій Володимирович; Безносик, Юрій Олександрович; Набок, Олександр Миколайович (Eastern-European Journal of Enterprise Technologies, 2014)
The issues of developing a mathematical model for calculating the aerodynamic drag and collection efficiency of solid particles in the cyclone collector, which takes into account the geometry and the opening angle of the louver element of designed dust collector, are considered in the paper. Experimental studies of the cyclone collector are given and the adequacy of the developed mathematical model is verified. Experimental data processing has allowed to determine the dimensionless coefficients n, m, l, included in the equation for determining fractional dust collection efficiency in the developed dust collector. Theoretical calculation of aerodynamic drag is conducted and the technique, suitable for the cyclone collector is determined by comparing with experimental results. The discrepancy between the experimental and theoretical data is 13.9 %. Dust collection efficiency is theoretically calculated using the mathematical model. The discrepancy between the experimental and theoretical data is 1.06 %. Experimental data processing is conducted and criterion equation for calculating partial coefficients of cleaning is found.